(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Depressive disorders loom large over the years when young people are forging identities, careers, and relationships. For those aged roughly 18–25 — a pivot point between adolescence and adulthood — the strain of exams, jobs, family expectations and shifting social worlds makes them uniquely vulnerable. Yet despite their visibility, depression in this group is often missed: symptoms can masquerade as moodiness or fatigue, and stigma too frequently keeps suffering hidden. Clinically, Major Depressive Disorder in young adults shares the core features seen at any age — persistent low mood, loss of interest or pleasure, and reduced energy — but it often wears different clothes. Irritability, disrupted sleep, withdrawal from friends and activities, and subtle declines in academic or occupational functioning may be the first clues. Because these presentations can be atypical, routine use of validated screening tools and a low threshold for asking about mood, sleep, appetite, concentration and suicidal thoughts are essential.